Relationship Marketing Activities in Building Customer-Oriented Marketing Services - Carragh Yutiana Ferguson; Hendi Paramita; Indira Ratnasari (Universitas Muhammadiyah Sidoarjo, 2021)
The aim of this study is to know how does relationship marketing activities in building customer-oriented marketing services. For this research, relationship marketing is used as it’s main theory, and the tool to conduct this research is through descriptive-qualitative methodology, with two informants from Singapore Intercultural School Bona Vista, first informant Head of Marketing of SIS Group of Schools and second informant Parents Relation Officer and Marketing Manager of Singapore Intercultural School Bona Vista as primary data. The research findings indicate that SIS Bona Vista has done well with their relationship marketing activities in building customer-oriented marketing services through pre sales mainly Digital: Website, Instagram, Facebook, Twitter, Google Ads, SEO, SEM where then they continue to email greeting such sharing information about the school, sending useful articles and in Traditional, reaching out to communities such Embassies of Korea and Japan. During sales when the target market visited Indonesia, they will book a school tour – “moment of truth” and an after sale an Alumni Group. Internal communication with existing parents it’s an open and flexible communication, through WhatsApp, email, Social Media. Parents and teacher through WhatsApp group. A weekly overall information through “SIS Connect” and internal application named “Academia”.